A generational divide?: Age-related aspects of political transformation in post-crisis Southern Europe - Freire, A.; Tsatsanis, E.; Lisi, M. (2023)
Freire, André, Xavier Coller, Paolo Segatti, Andrea Pedrazzani, Emmanouil Tsatsanis (2023), «Age cohorts and descriptive representation in Southern Europe: A general overview before and after the Great Recession», Emmanouil Tsatsanis, Marco Lisi & André Freire (editors) (2023), A Generational Divide? Age-related Aspects of Political Transformation in Post-crisis Southern Europe, London, Routledge., pp. 135-165.